2010
DOI: 10.1038/ijo.2010.177
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic consequences of the presence or absence of the thermogenic capacity of brown adipose tissue in mice (and probably in humans)

Abstract: Only with the development of the uncoupling protein 1 (UCP1)-ablated mouse has it become possible to strictly delineate the physiological significance of the thermogenic capacity of brown adipose tissue. Considering the presence of active brown adipose tissue in adult humans, these insights may have direct human implications. In addition to classical nonshivering thermogenesis, all adaptive adrenergic thermogeneses, including diet-induced thermogenesis, is fully dependent on brown adipocyte activity. Any weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
136
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(144 citation statements)
references
References 71 publications
8
136
0
Order By: Relevance
“…18 In this study, we observed that mRNA expression of Adrb3 in retroperitoneal fat was significantly higher in HFD than ND rats. Upregulation of Adrb3 is consistent with previous research demonstrating that adrenergic stimulation 8 via the b 3 -adrenergic receptor has a key role in brown fat activation and subsequent energy dissipation, 8 as well as emergence of brown fat in WAT. 20,39,46 Further, islands of brown adipocytes in WAT are richly sympathetically innervated.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…18 In this study, we observed that mRNA expression of Adrb3 in retroperitoneal fat was significantly higher in HFD than ND rats. Upregulation of Adrb3 is consistent with previous research demonstrating that adrenergic stimulation 8 via the b 3 -adrenergic receptor has a key role in brown fat activation and subsequent energy dissipation, 8 as well as emergence of brown fat in WAT. 20,39,46 Further, islands of brown adipocytes in WAT are richly sympathetically innervated.…”
Section: Discussionsupporting
confidence: 91%
“…1 Obesity is defined by the expansion of white adipose tissue (WAT), but recent evidence suggests that the adult human body also contains functionally distinct, brown adipose tissue. [2][3][4][5][6][7][8] In contrast to WAT, which has a primary role in energy storage, brown adipose tissue specializes in energy dissipation as heat (Cannon and Nedergaard 9 ). This thermogenic property of brown fat results from its high content of mitochondria, cell organelles where energy dissipation occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, shivering decreases during cold exposure after ∼2 weeks [47] and cold-stimulated activity has been shown to vary seasonally [4]. However, it remains unknown whether all or a portion of these effects can be directly attributed to adaptive BAT thermogenesis [48].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…However, whether the capacity to stimulate glucose uptake into BAT is also reduced under insulinresistant conditions is presently unknown. Since BAT relies on both carbohydrate and lipid oxidation for its heat production [21], an impaired glucose uptake under fasting-induced insulin-resistant conditions would hamper its thermogenic capacity and could lead to reduced capacity to defend body temperature upon cold exposure. On the other hand, if glucose uptake into BAT could be stimulated by cold exposure under such insulin-resistant conditions, activation of glucose uptake into BAT by cold exposure or other means could serve as an interesting target to increase glucose clearance during insulin resistance.…”
Section: Introductionmentioning
confidence: 99%